Russian Federation : Selected Issues. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper on the Russian Federation underlies inflation persistence and evolution in response to structural shocks. Inflation in Russia has been characterized by a considerable degree of persistence. An explicit inflation-targeting framework may help reduce firms' uncertainty about the future. This, in turn, may allow firms to be more forward-looking, thereby reducing persistence. The exchange rate is the Central Bank of Russia's (CBR) main policy instrument for controlling inflation. Allowing more nominal appreciation would help to keep inflation on a downward path and better anchor inflation expectations.